Recognition for Alphabet using Vector Scanning - Ogawa, Shuji; Matsuo*, Moriyuki (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
In this paper, it is considered a pattern from to be drawn each letter of the printed alphabet on the two-dimensional space and the new scanning method by using the rotation vector is clarified. Next some character patterns are made by expansion, reduction or inclining a letter. Then, each character pattern is scanned by rotation vector respectively. As a result alphabet space is composed. In the space, the distance between each letter is found. Keywords: Mutual-distance, Printed-alphabet, Character-pattern, Vector-scanning, Alphaber-space. E-mail: cast@kmitl.ac.th